Determining an optimal dose of linaclotide for use in Japanese patients with irritable bowel syndrome with constipation: A phase II randomized, double‐blind, placebo‐controlled study. Issue 5 (26th December 2017) - Fukudo, S.; Nakajima, A.; Fujiyama, Y.; Kosako, M.; Nakagawa, A.; Akiho, H.; Nakashima, Y.; Johnston, J. M.; Miwa, H.
Abstract: Background: Clinical testing to determine a suitable dose of linaclotide for Japanese patients with irritable bowel syndrome with constipation (IBS‐C) was needed. Methods: This was a randomized, double‐blind, placebo‐controlled, dose‐finding trial. Japanese patients with IBS‐C diagnosed using Rome III criteria (n = 559, men/women: 49/510) were randomly assigned to 1 of 4 linaclotide doses (0.0625, 0.125, 0.25, or 0.5 mg) or placebo for the 12‐week treatment period. The primary endpoint was responder rate of global assessment of relief of IBS symptoms during 12 weeks. The secondary endpoints included responder rates of complete spontaneous bowel movement (CSBM), SBM and abdominal pain/discomfort relief and others. Key Results: The primary endpoint was 23.2%, 36.2%, 38.7%, 34.8%, and 38.3% in placebo (n = 112), 0.0625 (n = 116), 0.125 (n = 111), 0.25 (n = 112), and 0.5 (n = 107) mg of linaclotide groups with the difference from the placebo group in each linaclotide group (13.0%, 15.5%, 11.6%, 15.1%, P  > .05). Monthly responder rate of global assessment of relief of IBS symptoms at month 3 (48.6%), responder rate of CSBM during 12 weeks (45.8%), and responder rate of abdominal pain/discomfort relief during 12 weeks (32.7%) in the 0.5 mg were significantly higher than those in placebo group (29.5%, P  < .01; 25.9%, P  < .01; and 18.8%, P  < .05 respectively). The most frequent adverse event in the linaclotide groups was diarrhea. Conclusions & Inferences: This study suggests that a linaclotide dose of 0.5 mg may be appropriate in Japanese patients with IBS‐C. Abstract : Linaclotide is approved for IBS with constipation (IBS‐C) in western countries at a dose of 0.29 mg. A phase II dose‐finding trial in Japan revealed that 0.5 mg/day of linaclotide was most effective on complete spontaneous bowel movement in IBS‐C patients. The finding of this study gives us a great hint of how guanylate cyclase C receptor activator works in IBS‐C patients with different genes, diet, gut microbiota, or other factors.